2004
DOI: 10.1167/iovs.03-1092
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of Hyalocytes under PDGF-Rich Conditions

Abstract: The hyalocytes demonstrated macrophage-like characteristics and may have both physiologic and pathologic roles, such as the maintenance of vitreous transparency through fibrinolytic activity and the pathogenesis of proliferative-vitreoretinal diseases through cellular proliferation and vitreous hyper-contraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 33 publications
2
45
0
Order By: Relevance
“…Cell culture. Bovine hyalocytes were isolated as we previously reported (33). Cultured hyalocytes obtained between passages 5 and 7 were used in experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell culture. Bovine hyalocytes were isolated as we previously reported (33). Cultured hyalocytes obtained between passages 5 and 7 were used in experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Collagen gel contraction assay. The contraction assay was performed as we previously described (33). Type I collagen (Koken, Tokyo), a reconstitution buffer, hyalocytes suspension, and distilled water were mixed and added to a 24-multiwell plate (Nunc, Roskilde, Denmark).…”
Section: Methodsmentioning
confidence: 99%
“…Morphological studies have demonstrated that hyalocytes, which possess lysosome-like granules, mitochondria, and micropinocytotic vesicles in their cytoplasm, belong to the monocyte/ macrophage lineage (22)(23)(24). They are considered to be originated from bone marrow and to regenerate in the vitreous cavity (25), as well as to be actively associated with the maintenance of vitreous transparency under physiological conditions (26,27).…”
mentioning
confidence: 99%
“…Collagen gel contraction assay. The contraction assay was performed as we previously described (24). Hyalocytes and BRPEs were collected by the treatment of cultures with trypsin-EDTA for 3 min, washed with DMEM, and resuspended in DMEM at a density of 2.2 ϫ 10 6 cells/ml.…”
Section: Methodsmentioning
confidence: 99%